Few-layer silicene nanosheets as saturable absorber for subpicosecond pulse generation in all-fiber laser. (November 2020) - Liu, Guowei; Yuan, Junjie; Lyu, Yudong; Wu, Tiange; Li, Zongwen; Zhu, Mingxiao; Zhang, Fang; Xing, Fei; Zhang, Wenfei; Zhang, Huanian; Fu, Shenggui
Highlights: Silicene has a lower saturation intensity and a higher value of modulate depth at 1550 nm (20%). It is the first time to achieve ultrafast fiber laser based on few-layer silicene nanosheets as SA. Our research broadened the application of 2D-Si at the optical communication technologies. Abstract: Two-dimensional silicene nanosheets is an emerging material in many fields. However, there is a lack of research on nonlinear optical applications of silicene nanosheets so far. Here, we demonstrate a subpicosecond soliton mode-locked erbium-doped fiber laser using microfiber-based silicene nanosheets as a saturable absorber for the first time, to the best of our knowledge. Few-layer silicene nanosheets, which were prepared by liquid-phase exfoliation method, have a modulation depth is 20% and the saturation intensity is 5.78 MW/cm 2 . Stable soliton pulses were generated at 1531.48 nm with a 3-dB bandwidth of 2.84 nm, a pulse duration of 937 fs, and a time-bandwidth product of 0.34. Our results indicate that few-layer silicene nanosheets could be used as an excellent photonic device for short-pulse laser, and promote the applications of silicene-based nonlinear photonics.